Analisis Pemahaman Akuntansi, Sistem Informasi Akuntansi, dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan UMKM - Sugiharto, Bagus Hari (Jurnal EMT KITA, 2026)
This study aims to examine how understanding of accounting, accounting information systems, and internal control systems affect the quality of financial reports of small and medium enterprises (MSMEs) located in Pasuruan City. This study uses a quantitative method based on a questionnaire. By using multiple linear regression, partial data analysis was conducted. The results of the study for partial evidence indicate that understanding of accounting and internal control systems significantly affect the quality of MSMEs' financial reports, but the results of accounting information systems do not significantly affect the quality of MSMEs' financial reports. Simultaneous testing shows that understanding of accounting and internal control systems significantly affect the quality of MSMEs' financial reports. The R square result is 42.3%.